PENGEMBANGAN BAHAN AJAR MATEMATIKA SD BERNUANSA MELAYU - Nurul Ul Husna Nasution; Sukmawarti Sukmawarti (Sekolah Tinggi Pariwisata Mataram, 2022)
The development of elementary mathematics teaching materials with Malay cultural nuances for fourth grade elementary school is motivated by the absence of mathematics teaching materials based on Malay cultural values ​​to get a positive response from students because the teaching materials used are still general in nature so that regional nuances are far from students. So, there is a need for innovation in instilling real mathematical concepts through pictures of sites or historical objects that are around in order to contribute to students' understanding of Malay culture-based teaching materials so that mathematics teaching materials are more in touch with the student's world on geometry material, especially flat wake materials. This study aims to develop mathematics teaching materials with Malay cultural nuances on geometry material in the fourth grade of elementary school. This development research uses the Research and development (R&D) research method with the ADDIE model research method (Analysis, Design, Development, Implementation, and Evaluation). This research is basically carried out through five main stages, namely the analysis stage, the design stage, the development stage, the implementation stage, and the evaluation stage. This research only reached the development stage and did not reach the evaluation stage. This study uses a questionnaire as a tool to test the feasibility of learning teaching materials through the validation of material experts, media experts and teacher responses. The results of the development obtained are the product of teaching materials for learning mathematics in the fourth grade elementary school grade flat shape material. The teaching materials developed were validated by material experts, media experts and teacher responses. After the validation process was carried out by material experts, media experts and teacher responses, which were then revised and produced textbooks that were appropriate for fourth grade elementary school students. Thus the learning teaching materials developed were declared suitable for use in learning.